Missed Opportunities for Human Immunodeficiency Virus and Syphilis Testing Among Men Who Have Sex With Men in China: A Cross-Sectional Study. Issue 6 (June 2018) - Ong, Jason J.; Fu, Hongyun; Pan, Stephen; Smith, M. Kumi; Wu, Dan; Wei, Chongyi; Cao, Bolin; Ma, Wei; Yang, Ligang; Tang, Weiming; Tucker, Joseph D.
Abstract : Background: Men who have sex with men (MSM) are at high risk of human immunodeficiency virus (HIV)/syphilis. To inform strategies for dual testing, we describe patterns of HIV/syphilis testing, and examine factors associated with never testing for HIV/syphilis in China. Methods: An online survey (2016) was completed by MSM from 8 cities: men born biologically male, 16 years or older, and had sex with another man at least once during their lifetime. Demographic, sexual behavioral, and HIV/syphilis testing data were collected. Multivariable multinomial logistic regression identified characteristics associated with men who never tested for HIV/syphilis compared with men who ever tested for both infections. Results: Overall, 2105 men participated. Among them, 35.1% (738/2105) never tested for HIV/syphilis, and in those ever tested for HIV, only half (54.0%, 709/1312) had tested for syphilis. Relative to men who had ever tested for both infections, those with increased probability of never testing for HIV/syphilis include non-gay sexual identity (prevalence odds ratio [POR] 1.86; 95% confidence interval [CI], 1.45–2.37), not disclosed their sexuality/sexual history with men other than their regular partner (POR, 2.22; 95% CI, 1.75–2.78]) or with health professionals (POR, 11.11; 95% CI, 7.69–14.29), no condomless sex with casual partners in the last 3 months (POR, 1.89; 95% CI, 1.37–2.56), no community engagement in sexual health (POR, 15.16; 95% CI, 9.40–24.45), and mainly met partners offline (POR, 1.49; 95% CI, 1.16–1.92). Conclusions: There are significant gaps in lifetime testing for HIV/syphilis among Chinese MSM. Strategies to target never testers and integrate syphilis testing within HIV testing services are urgently needed. Future opportunities include point-of-care dual test kits, and testing in China's expanding primary healthcare system. Abstract : A study of men who have sex with men in China revealed 35% had never tested for human immunodeficiency virus/syphilis, and among human immunodeficiency virus testers, only 51% had ever tested for syphilis.